2016
DOI: 10.1038/srep24389
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial cell migration requires the interaction between the vimentin and keratin intermediate filaments

Abstract: Epithelial migration plays a central role in development, wound repair and tumor metastasis, but the role of intermediate filament in this important event is unknown. We showed recently that vimentin coexists in the same cell with keratin-KRT14 at the leading edge of the migrating epidermal cells, and knockdown of vimentin impaired colony growth. Here we demonstrate that vimentin co-localizes and co-immunoprecipitates with keratin-KRT14, and mutations in the -YRKLLEGEE- sequence of vimentin significantly reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 53 publications
5
42
0
Order By: Relevance
“…Unlike mesenchymal cells, epithelial cells have the ability to migrate only during development or tissue renewal, such in the gut or wound repair [122]. To be able to migrate, tumor cells have to acquire the ability to get rid of the cell-cell contacts, cross the basal membrane, cross the stroma, enter the circulatory system, invade a new distal site and colonize the new organ.…”
Section: Hallmarking Cancermentioning
confidence: 99%
“…Unlike mesenchymal cells, epithelial cells have the ability to migrate only during development or tissue renewal, such in the gut or wound repair [122]. To be able to migrate, tumor cells have to acquire the ability to get rid of the cell-cell contacts, cross the basal membrane, cross the stroma, enter the circulatory system, invade a new distal site and colonize the new organ.…”
Section: Hallmarking Cancermentioning
confidence: 99%
“…Vimentin could be found in the cell in different forms: nonfilamentous particles, ULFs, and mature IF filaments. It has been shown that vimentin IFs in epithelial cells are preferably located at the leading edge of the cell (Velez‐Delvalle et al, ), while in fibroblasts IFs are mostly observed in the rear parts of the cells (Helfand et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Vimentin and keratin coexist in keratinocytes or some metastatic cells [228,229]. It has been shown that mutation in vimentin reduced the migration of keratinocytes [230]. So, the different structural (number of monomers per cross section, 16 for keratin and 32 for vimentin) and mechanical (vimentin is stiffer than keratin) properties of keratin and vimentin lead to different behaviour of cells.…”
Section: Resultsmentioning
confidence: 99%